Assessment of the role of small mammals in the transmission cycle of tegumentary leishmaniasis and first report of natural infection with Leishmania braziliensis in two sigmodontines in northeastern Argentina - Fernández, María Soledad (2018)
To contribute to the knowledge of the role of small mammals in the transmission cycle of tegumentary leishmaniasis caused by Leishmania braziliensis, we studied the small mammal community and its temporal and spatial association with phlebotominae, as well as small mammal infection by Leishmania spp. by PCR-RFLP analyses in an endemic area of northeastern Argentina. Ten small mammal samplings were conducted (2007–2009, 7506 Sherman trap nights and 422 cage trap nights). In two of these samplings, 16 capture stations each one consisting of a CDC light trap to capture phlebotominae, two to four Sherman traps and two cage traps were placed. We found co-occurrence of phlebotominae and small mammal captures in four stations, which were all the stations with small mammal captures and yielded 97% (2295 specimens, including 21 gravid females) of the total phlebotominae captures, suggesting that small mammals may provide a potential source of blood for phlebotominae females. One Didelphis albiventris and two Rattus rattus were associated with high captures of Nyssomyia whitmani, vector of L. braziliensis in the study area. The PCR-RFLP analyses confirm the presence of L. braziliensis in two sigmodontine small mammals (Akodon sp. and Euryoryzomys russatus) for the first time in Argentina, to our knowledge.